2014
DOI: 10.1016/j.cattod.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Chemically activated poly(furfuryl alcohol)-derived CMK-3 carbon catalysts for the oxidative dehydrogenation of ethylbenzene

Abstract: The surface of CMK-3 carbon, synthesized by the reversible replication of mesoporous silica (SBA-15) using poly(furfuryl alcohol) as a carbon precursor, was activated by wet oxidation with an aqueous solution of HNO 3 or H 2 O 2 . The process was performed at 50°C using solution containing different concentrations of the oxidizing agent. It was found that during the modification no significant changes in textural and structural properties of CMK-3 replica occurred. However, the treatment resulted in the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Ordered mesoporous carbon materials synthesized by various methods and pre-treated at different conditions exhibited earlier a very similar behaviour in the oxidative dehydrogenation of ethylbenzene [21]. It was found that during this process the surface oxygencontaining species generated during the synthesis and subsequent modifications were lost by decomposition and/or re-arrangement (connected with the formation of carbon deposit) and, in consequence, similar activity was observed after some hours on stream over all materials [21,23,24]. Figure 8 summarizes the variations in selectivity to propene vs. TOS.…”
Section: Catalytic Activity Of Cmk-3 Catalystsmentioning
confidence: 70%
“…Ordered mesoporous carbon materials synthesized by various methods and pre-treated at different conditions exhibited earlier a very similar behaviour in the oxidative dehydrogenation of ethylbenzene [21]. It was found that during this process the surface oxygencontaining species generated during the synthesis and subsequent modifications were lost by decomposition and/or re-arrangement (connected with the formation of carbon deposit) and, in consequence, similar activity was observed after some hours on stream over all materials [21,23,24]. Figure 8 summarizes the variations in selectivity to propene vs. TOS.…”
Section: Catalytic Activity Of Cmk-3 Catalystsmentioning
confidence: 70%
“…soot, graphite, carbon nanofilaments [14], activated carbons [16,17], multi-walled carbon nanotubes, onion-like carbons [18,19], nanodiamonds [20]) were tested in M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 ODH. Among them, CMK-type materials showed a very attractive catalytic activity [8,[21][22][23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In particular, mesoporous carbons with high surface area, ordered structure and pore dimension between 2 and 50 nm, increase the mass transfer, limited in active carbon supports . The main challenge in the application of the mesoporous carbon as metal‐free catalyst is to prepare a well ordered structure with a controlled degree of functionalization ,…”
Section: Introductionmentioning
confidence: 99%
“…[5] The main challenge in the application of the mesoporous carbon as metal-free catalyst is to prepare a well ordered structure with a controlled degree of functionalization. [6,7] The ordered mesoporous carbon structure can be obtained by the replica method, through a sacrificial templating agent that controls the order degree and the formation of mesopores. [8] The soft templating method is generally preferred to the hard templating ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation